The second issue of the semi-annual Montage/AV - Mareš, Petr (Iluminace, 1993)
A review of the second issue of the German journal Montage/AV, focusing on popular culture and especially on the work of its influential contemporary theorist John Fiske.
Keywords: film theory; film periodicals; montage/av; pop culture; John Fiske